Perancangan Ensiklopedia Digital Interaktif Tokoh Wayang Kulit Cirebon pada Mobile Device - Bima Nurin Aulan; Irfansyah Irfansyah; Alvanov Zpalanzani Mansoor (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Cirebonese shadow puppet (wayang kulit) is one of the traditional Indonesian wayang cultures. Located in the north beach of Java, the city of Cirebon once functioned as a trading port for foreign merchants from all over China, Arabia and India. While selling their local goodies, the activities triggered an exchange of cultures between the foreign traders and the Indonesians. One of the results from the acculturation is Cirebonese shadow puppet. It combines the root story of Ramayana-Mahabharata from India, Islamic stories from Arabia, and unique color schemes from China. The accelerating technological development today can affect the existence of traditional literature like Cirebonese shadow puppets. The idea is, if we could convert the traditional literature into digital format, we could extend their lives for further development.The main objective of the research is the characters of the Cirebonese shadow puppet. First, they will be classified into several groups based on the story and type of wayang. The research will utilize the typological method and the analysis will be categorized based on the class/rank of wayang, e.g. characters of satria, raksasa (giant), god and goddess. And then we will break-down to the semiotic values from their visual attributes, such as ornaments. The data will be used as the basis in designing interactive application for popular digital media devices. Visual styles, layouts and compositions will be adjusted according to popular design styles of the present day. As a forecast, the design could be constantly modified also further developed within 2 to 5 years ahead. We hope the outcome of the project can enliven the Cirebonese shadow puppet to the next level and inspire other designers and researchers for further development, creating a sustainable future for Indonesian wayang culture.